2022
DOI: 10.1007/s00701-022-05216-8
|View full text |Cite
|
Sign up to set email alerts
|

External validation of prognostic models predicting outcome after chronic subdural hematoma

Abstract: Background Several prognostic models for outcomes after chronic subdural hematoma (CSDH) treatment have been published in recent years. However, these models are not sufficiently validated for use in daily clinical practice. We aimed to assess the performance of existing prediction models for outcomes in patients diagnosed with CSDH. Methods We systematically searched relevant literature databases up to February 2021 to identify prognostic models for outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In recent years, several models predicting the recurrence of CSDH after surgery have been published. To evaluate the performance of these existing models in predicting postoperative recurrence in CSDH patients, Holl et al ( 13 ) utilized a retrospective database comprising data from 2,384 patients across three regions in the Netherlands. The study revealed that current predictive models perform poorly on the author’s dataset, failing to effectively forecast the recurrence of hematomas following CSDH treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several models predicting the recurrence of CSDH after surgery have been published. To evaluate the performance of these existing models in predicting postoperative recurrence in CSDH patients, Holl et al ( 13 ) utilized a retrospective database comprising data from 2,384 patients across three regions in the Netherlands. The study revealed that current predictive models perform poorly on the author’s dataset, failing to effectively forecast the recurrence of hematomas following CSDH treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] These models attempted to predict outcome measures of CSDH such as mortality, risk of recurrence, and functional outcome after surgical treatment. 2 Population differences and differences in the distribution of predictors between development and validation studies may affect model performance in the validation setting. 2 The factors that affect prognosis may vary greatly at different follow-up times.…”
Section: Introductionmentioning
confidence: 99%
“…2 Population differences and differences in the distribution of predictors between development and validation studies may affect model performance in the validation setting. 2 The factors that affect prognosis may vary greatly at different follow-up times. Due to drain removal, a repeat head computed tomography (CT) 1 week after the burr hole and drainage tended to show an increased residual cavity volume.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations